2022
DOI: 10.3389/fonc.2022.802467
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Low-Dose Nab-Paclitaxel Plus Tislelizumab in Elderly Patients With Previously Treated Metastatic Non-Small Cell Lung Cancer

Abstract: The combination of immunotherapy and chemotherapy has a synergic effect in non-small cell lung cancer (NSCLC). However, the elderly are often excluded from clinical trails due to their poor health status and more comorbidities. We sought to assess the efficacy and safety of low-dose nanoparticle albumin-bound paclitaxel (nab-paclitaxel) plus tislelizumab (an anti-PD-1 antibody) in elderly patients with advanced NSCLC. In this phase 2 clinical trail, eligible patients were those aged ≥65 years with metastatic N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…These results suggest that reduced‐dose chemotherapy, plus immunotherapy benefits elderly and frail patients. Similarly, the promising efficacy of reduced‐dose nab‐paclitaxel plus tislelizumab in elderly patients was corroborated in a phase II Chinese clinical trial 17 . The study included patients with LUAD and LUSC; the ORR and PFS were 34.5% and 9.5 months (95% CI, 5.8–13.2), respectively.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…These results suggest that reduced‐dose chemotherapy, plus immunotherapy benefits elderly and frail patients. Similarly, the promising efficacy of reduced‐dose nab‐paclitaxel plus tislelizumab in elderly patients was corroborated in a phase II Chinese clinical trial 17 . The study included patients with LUAD and LUSC; the ORR and PFS were 34.5% and 9.5 months (95% CI, 5.8–13.2), respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Recent literature indicates that reduced‐dose chemotherapy is as effective as full‐dose chemotherapy in elderly patients 17,19 . In addition, some studies have demonstrated that reduced‐dose chemotherapy can enhance antigen release, remodel the active LUSC immune microenvironment, and increase synergistic effects 20–22 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations